EFEKTIVITAS MODEL LSQ DALAM MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA PADA KELAS V SD INPRES 4/82 BAJOE KABUPATEN BONE - Rosmalah, Rosmalah; Firdaus, Firdaus; Hasfirawati, Hasfirawati (JPPSD: Jurnal Pendidikan dan Pembelajaran Sekolah Dasar, 2024)
This research is a quantitative research type experiment that aims to determine the effectiveness of the LSQ model on students' mathematics learning outcomes.The research design used One Group Pretest-Posttest Design. The population in this study were fifth grade students of SD Inpres 4/82 Bajoe. The data collection techniques used were tests, questionnaires and observation sheets. The data analysis used was descriptive and inferential statistical analysis. Based on the results of descriptive statistical analysis, the average pretest 32.50 posttest 68.16 was obtained. The average response questionnaire was 86.25 and the learning implementation was 93.33. While the results of inferential statistical analysis show that pretest and posttest data are normally distributed. The homogeneity test shows that the pretest and posttest are homogeneous. While the Hypothesis test shows that the Sig value is 0.000 <0.05, meaning that there is a difference. So it can be concluded that the LSQ Model is effectively used in learning student mathematics in class V of SD Inpres 4/82 Bajoe, East Tanete Riattang District, Bone Regency.